Analysis of Training Load During the Special Preparation and Competition Periods Using Physiological Indicators in U19 Football Players via Smart Bracelet - Abd , Yousef; Hamoud , Mahdi; Hamed , Safwan; Hassan , Jassim (Journal of Physical Education, 2025)
The importance of the study lies in highlighting the role of smartwatches as a modern tool for analyzing training load based on functional indicators, such as heart rate and calorie consumption. This allows coaches to monitor individual players’ responses during different training periods, helping to improve physical performance efficiency and reduce the risk of overload-induced fatigue. The study aimed to analyze calorie consumption at different heart rate levels between the special preparation and competition periods for youth football players, with the goal of determining the effect of physiological adaptation on energy efficiency. To achieve this objective, the researcher adopted the descriptive method due to its suitability for the nature of the study. A purposive simple sample of 20 youth players representing the youth team of Al-Quwa Al-Jawiya Club was selected, with weights ranging between 60–75 kg. A pilot experiment was conducted on a small sample of players to test the accuracy of smartwatches in measuring heart rate and calorie consumption by comparing them with standard measurement devices. The results showed good agreement in heart rate measurement and a slight deviation in calorie consumption, confirming their validity for use in the study after calibration.